Social Mobility in the Post-Soviet Russia: A Revision of Existing Measurements by Drawing on Advanced Methods - Yastrebov, Gordey (Journal of Economic Sociology, 2014)
Most of existing studies of social mobility in the post-Soviet Russia provide measurements in terms of absolute mobility. However, the problem with such measurements is that they do not account for the structural differences when applied for cross-temporal (or cross-national) comparisons (which might be caused, for instance, by the change in the relative number of certain occupations, the expansion of higher education, etc.). Thus, absolute mobility (be it downward, upward or no mobility at all) does not distinguish the change which is caused by the institutional (i.e. qualitative), rather than the structural (i.e. quantitative) change. In this project we aim to fill in this gap and to analyze the dynamics of relative social mobility (i.e. mobility “net” of structural factors) in the post-Soviet period. Precisely, we would use the so called log-linear and log-multiplicative models designed to analyze contingency tables. By social mobility in this research we will understand intra- and intergenerational individual shifts in terms of occupational status, education and spatial (i.e. urban/rural) location. The data we will use come from representative surveys conducted in 1994, 2002, 2006 (2013 is work-in-progress at the stage of grant application). The surveys were initially designed by professor Shkaratan for the purpose of studying mobility and stratification processes in modern Russia. In order to guarantee the accuracy of our results we also intend to run parallel estimations by drawing on alternative data (RLMS, Generations & Gender Survey, International Social Survey Programme and European Social Survey).